Gut Fecal Microbiota Transplant in a Mouse Model of Orthotopic Rectal Cancer - Chen, Yen-Cheng; Miao, Zhi-Feng; Yip, Kwan-Ling; Cheng, Yi-An; Liu, Chung-Jung; Li, Ling-Hui; Lin, Chung-Yen; Wang, Jiunn-Wei; Wu, Deng-Chyang; Cheng, Tian-Lu; Wang, Jaw-Yuan (Frontiers in Oncology, 2020)
The gut microbiota is reported to play an important role in carcinogenesis and the treatment of CRC. SW480 and SW620 colon cancer cells integrated with infrared fluorescent proteins were injected into the rectal submucosa of nude mice. In the subsequent 30 days, we observed tumor growth weekly using an in vivo imaging system. The bacterial solution was infused anally into the mice to perform bacterial transplant. Phosphate-buffered saline, Acinetobacter lwoffii, and Bifidobacterium longum solutions were infused individually. The 16S ribosomal DNA (rDNA) and polymerase chain reaction of murine feces were investigated to confirm the colonization of target bacteria. In the SW620 orthotopic xenograft rectal cancer model, 4 of 5 mice developed rectal cancer by 30 days after submucosal injection. In the SW480 orthotopic xenograft rectal cancer model, 2 of 6 mice developed rectal cancer by 30 days after submucosal injection. For the 16S rDNA analysis, the mice receiving the bacterial solution infusion demonstrated positive findings for A. lwoffii and B. longum. With the successful establishment of a mouse model of orthotopic rectal cancer and transplant of target bacteria, we can further explore the relationship between gut microbiota and CRC. The role of fecal microbiota transplant in the treatment and alleviation of adverse events of chemotherapy in CRC could be clarified in subsequent studies.